IMPLEMENTATION OF REGIONAL PERATURAH NUMBER 8 2015 ON HIV/AIDS PREVENTION AND CONTROL (CASE STUDY AT KARIMUN DISTRICT AIDS COMMISSION OFFICE) - Kurniawati; Kasirul Fadli; Frinda Novita; Azmi; Rolly Sambuardi (Indonesian Journal of Social Sciences, Policy and Politics, 2023)
This research aims to determine the implementation of Regional Regulation Number 8 of 2015 concerning the Prevention and Control of HIV/AIDS (Case Study at the Karimun Regency AIDS Commission Office) and to find out what factors support and inhibit its implementation. that policy. Data collection methods in this research used field observation, unstructured interviews, and documentation. The data analysis used in this research is a qualitative data analysis method. The results of the research show that the Karimun Regency AIDS Control Commission has not succeeded in reducing or eliminating the spread of HIV/AIDS in Karimun Regency from 66 HIV cases, 19 AIDS cases with 1 death due to AIDS in 2020 to 69 HIV cases, 5 AIDS cases with a death rate due to There is zero AIDS in 2021, and of the 52 HIV cases, there are 3 AIDS cases with the number of deaths due to AIDS being 2 cases in 2022. Implementation of the HIV/AIDS prevention and control program in Karimun Regency has not run optimally due to the lack of public knowledge regarding regional regulations, limitations human resources and budget, as well as the lack of awareness of policy implementers in implementing them.